PERTANGGUNGJAWABAN ORANG TUA TERHADAP ANAK INCEST MENURUT HUKUM ISLAM - KHAIRI AYUMI HASAN (PREMISE LAW JURNAL, 2016)
Based on the Islamic criminal law, the incest performer is handed down a death sentence as referred to Prophet Muhammad’s words retold by Abdullah Bin Abbas ‘whoever has a sexual intercourse with his mahram (immediate/close relative), kill him”. The parents are responsible for their children in line with Al-Quran Surah i.e. Al-Baqarah, verse 233. One of the parents’ responsibilities for their incestuous child’s is to provide the custody. Based on the Islamic law, the custody of the incestuous child is given to his/her mother. In case she cannot take care of the child because she is not eligible for the custody; according to the Islamic law, it is transferred to his/her mother’s relatives. An incestuous child does not have a kinship (nasab Consequently, based on the Islamic inheritance law, an incestuous child does not have any rights on the inheritance left by his/her father. However, according to Imam Syafi’i in the Compilation of the Islamic Laws Article 186, an incestuous child has the inheritance relationship from his/her mother and relatives from his/her mother side. Keywords: Responsibility, Incestuous Child,  Islamic Law